Interprofessional Climate Change Curriculum in Health Professional Programs: A Scoping Review - Trisha Dalapati; Sophie E. Nick; Tristan A. Chari; Ian A. George; Alexandra Hunter Aitchison; Mark P. MacEachern; Aine N. O'Sullivan; Kreager A. Taber; Andrew Muzyk (MDPI AG, 2023)
Background: We conducted this scoping review to (1) comprehensively compile the published literature on interprofessional education focused on climate change and health, (2) assess the quality and outcomes of the existing curriculum interventions, and (3) highlight potential areas for further growth. By evaluating published curricular interventions, our goal was to highlight effective and validated developments that could be utilized by health professional educators seeking to include topics on climate change in the curriculum. Methods: We searched Ovid MEDLINE databases (MEDLINE, In-Process, In-Data-Review and Other Non-Indexed Citations, and Epub Ahead of Print), Embase, Clarivate Web of Science, and EBSCOhost Education Abstracts from inception through March 2023. Resulting articles were screened for relevance, and data were extracted from the included studies. The Medical Education Research Study Quality Instrument (MERSQI) was used to assess the quality of each included study. Findings: We screened 688 unique articles, and 6 met inclusion criteria. Publications dated from 2013 to 2023. Three studies included students or healthcare professionals from at least three health profession education programs. The mean MERSQI score was 8·17 (SD = 1·34; range 6-10). Curricular interventions varied by study, and topics included effects of climate change on human health, effect of climate change on extreme weather events and infectious disease exposures, and role of health professionals in climate change communication. Studies did not utilize a two-group comparison design. Most studies used an assessment tool with content validity evidence, but no study provided evidence of validity for internal structure or relationships to other variables. Studies reported that curricular interventions improved outcomes related to both climate change and interprofessional education. Interpretation: Despite the growing call for health professional education focused on climate change and health, there remains a gap in the interprofessional curricular interventions that have been assessed.